1982
DOI: 10.1017/s0144686x0000917x
|View full text |Cite
|
Sign up to set email alerts
|

Ageing, Development and Social Service Delivery Systems in Latin America: Problems and Perspectives

Abstract: Economic development in Latin America has facilitated the broadening and improvement of governmental services in public health, social security and public administration. These improvements, particularly in public health, have precipitated changes in rates of morbidity and mortality. Many countries have also experienced a fall in birth rates during this period. The result of people living longer and having fewer children is a progressive ageing of Latin American societies. This article explores some critical q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
1994
1994

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…They include efforts to raise consciousness of conditions affecting older people, and represent their interests in various community arenas. There is no single strategy which typifies these initiatives in Latin America, or in other areas described in the literature (Checkoway 1988;Minkler 1988;Kerschner 1990 a, 1990 b;Ministerio de Salud 1985a;Tapia-Videla and Parrish 1982).…”
Section: Perspectives On Practicementioning
confidence: 99%
“…They include efforts to raise consciousness of conditions affecting older people, and represent their interests in various community arenas. There is no single strategy which typifies these initiatives in Latin America, or in other areas described in the literature (Checkoway 1988;Minkler 1988;Kerschner 1990 a, 1990 b;Ministerio de Salud 1985a;Tapia-Videla and Parrish 1982).…”
Section: Perspectives On Practicementioning
confidence: 99%
“…In the early 1980s Tapia-Videla and Parrish observed that: 'No Latin American country has developed a service continuum offering a wide number of alternative options'. 24 But in the 1990s it appears that Costa Rica is progressing towards this and establishing institutions for intersectoral collaboration among them.…”
Section: Opportunities and Obstaclesmentioning
confidence: 99%